Bilateral perisylvian ulegyria: An under‐recognized, surgically remediable epileptic syndrome. Issue 8 (15th April 2013) - Schilling, Lucas P.; Kieling, Renata R.; Pascoal, Tharick A.; Kim, Hyoung‐Ihl; Lee, Min Cheol; Kim, Yun Hee; Paglioli, Eliseu; Neto, Pedro R.; Costa, Jaderson C.; Palmini, Andre
Summary Purpose Interest in the association of epilepsy and pseudobulbar palsy was rekindled since the identification through magnetic resonance imaging (MRI) of bilateral perisylvian polymicrogyria (PMG). Seizures are often intractable, but resective epilepsy surgery has not been recommended. However, a similar clinical picture can be encountered in patients with bilateral perisylvian destructive lesions, which fit the description of ulegyria (ULG). We report a series of patients with epilepsy and pseudobulbar palsy due to bilateral perisylvian ULG (BP‐ULG), show that hippocampal sclerosis (HS) is often associated and highlight the fact that in this entity, unlike in malformative bilateral perisylvian PMG, seizures may be surgically treated. Methods The motor, cognitive, epileptologic, and imaging features of 12 patients with perisylvian ULG followed at three institutions are described. For patients with refractory seizures, we detail extracranial and intracranial electrographic recordings, surgical strategies, histopathologic analyses of the resected tissue, and outcome of surgical treatment. Descriptive statistics were used for quantitative and categorical variables. Student's t‐test was used to compare means, and a p < 0.05 was considered significant. Key Findings Pseudobulbar palsy and mental retardation were present in all patients with symmetrical BP‐ULG. Five had refractory seizures. There was no relationship between the severity of the pseudobulbar palsy or of the mental retardation and the degree of seizure control with medication. The five patients in whom seizures were refractory to medication had significantly earlier age of onset and longer duration of epilepsy (p < 0.05). Dual pathology with associated unilateral HS was present in four. One patient with dual pathology had a temporolimbic electroclinical picture and had an anterior temporal lobectomy (ATL) based upon noninvasive evaluation. The other four had ictal semiology suggesting involvement of both temporolimbic and perisylvian cortex. Intracranial electroencephalography (EEG) showed concomitant seizure onset in the anterior temporal region and in the ipsilateral ULG in three of the four with dual pathology and in the ulegyric cortex in the one without HS. Resection guided by a combination of semiology, MRI, and extra and intracranial EEG led to complete seizure control in two and almost complete seizure control (Engel class II) in two other patients. The only surgical failure was an isolated ATL in a patient with dual pathology, and concomitant seizure onset in both lesions according to semiology and intracranial EEG. Significance Our findings suggest that BP‐ULG mimics the clinical features of bilateral perisylvian PMG. In patients with refractory seizures, recognition of this entity should lead to consideration of resective surgery despite the bilateral ULG.